Acute Hepatitis Induced by Alpha-Interferon in a Patient with Chronic Hepatitis C - Ivan Kraus; Dinko Vitezic (Canadian Journal of Gastroenterology)
Hepatic adverse effects occur very rarely with alpha-interferon therapy. A case of acute hepatitis induced by alpha-interferon in a 33-year-old man with chronic hepatitis C is described. The patient developed acute hepatitis with very high aminotransferase activity and jaundice. After discontinuing alpha-interferon therapy, hepatitis resolved rapidly. The immune-mediated mechanism is the most probable cause of this hepatitis.